Generation of gene disruptions by transcription activator-like effector nucleases (TALENs) in Xenopus tropicalis embryos - Lei, Yong (BioMed Central, 2013)
Transcription activator-like effector nucleases (TALENs) are novel engineered DNA nucleases, and have been proven to be effective for gene specific targeting in various species. Recently we reported gene disruptions in Xenopus embryos by using TALENs. Here we summarize the protocol that is used in our studies for gene disruption. This protocol covers selection of TALEN targeting sites, TALEN assembly with a modified Golden Gate method, and injection of TALEN mRNAs into Xenopus tropicalis embryos. We also provide details for detection of somatic and germ line transmitted mutations. And finally, we briefly describe establishment of knockout Xenopus lines. This protocol will facilitate broader applications of TALENs in studies of Xenopus biology.